Evil: a challenge against moral perfectibility and juridical ordering. An essay starting from Kantian philosophy - Lenis Castaño, John Fredy (Estudios de Filosofía, 2003)
The problem of evil, that becomes concrete as banalization and destruction of humanity itself is a challange for all societies, both as formation (Bildung) and in relation to political-juridical institutions Kantian philosophy assumes this challenge and proposes an ethical-political project that passes through that which is pedagogical and aesthetic. The purpose of this amide is to conduct an exploration of the possibilities of moral and juridical configuration of subjects starting from Kantian proposals, contrasting them with the permanent difficulty that radical evil is. To do so, this will be done using four stages. The first will ducuss the anthropological assumptions or human features that become a condition of possibility of both moralisation and of normalization. The second will deal with the topic of ethical-moral legislation and it goes profoundly into the concept of autonomy. The third will propose a relation between ethics and politics, by using the juridical as mean, so that it may finally draw up some conclusions.